2015
DOI: 10.3748/wjg.v21.i28.8615
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 upregulates CBS expression through NF-κB activation in a rat model of irritable bowel syndrome with chronic visceral hypersensitivity

Abstract: Our results suggest that the activation of TLR4 by NCI upregulates CBS expression, which is mediated by the NF-κB signaling pathway, thus contributing to visceral hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
4
19
0
Order By: Relevance
“…In the present study, the microbial composition of MS group gut communities was associated with the enhanced functional capacity for the NF-kappa B signaling pathway. This result is consistent with previous studies indicating that neonatal MS induces VH and visceral pain in rats that is mediated by activation of TLR4 and the NF-κB signaling pathway [27,28] and further suggests that changes in the gut microbiomes caused by MS are involved in NF-κB activation in a rat model of IBS.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the microbial composition of MS group gut communities was associated with the enhanced functional capacity for the NF-kappa B signaling pathway. This result is consistent with previous studies indicating that neonatal MS induces VH and visceral pain in rats that is mediated by activation of TLR4 and the NF-κB signaling pathway [27,28] and further suggests that changes in the gut microbiomes caused by MS are involved in NF-κB activation in a rat model of IBS.…”
Section: Discussionsupporting
confidence: 93%
“…That periostin mediates intestinal inflammation via the activation of NF-κB pathway, which suggests that periostin may be a potential therapeutic target for inflammatory bowel disease [ 30 ] has been reported. One latest study showed that the activation of TLR4 by NCI increase CBS expression, which is mediated by the NF-κB pathway, final lead to visceral hypersensitivity [ 31 ]. In our research, we found that NF-κB p65 of model group was up-regulated, and after the inhibitor of NF-κB pathway, the expression of NF-κB p65 was down-regulated again, which revealed NF-κB pathway played a role in the mechanism of IBS.…”
Section: Discussionmentioning
confidence: 99%
“…Tamizhselvi et al [50] reported that H 2 S may up-regulate the TLR4 pathway via substance P. In accordance, our in-vitro experiment showed that the downregulation of H 2 S could markedly activate the TLR4 expression in the mouse mesangial cells. Vice versa, TLR4 was reported to upregulate CBS expression through NF-κB activation in rat [51]. Zheng et al found that compared with their wide-type counterparts, TLR4 knockout mice showed elevated expression of H 2 S-synthesizing enzyme CSE, therefore abolishing the inflammation effect of lipopolysaccharide [52].…”
Section: Discussionmentioning
confidence: 99%